2016
DOI: 10.1093/mnras/stw2056
|View full text |Cite
|
Sign up to set email alerts
|

The mass dependence of star formation histories in barred spiral galaxies

Abstract: We performed a series of 29 gasdynamical simulations of disc galaxies, barred and unbarred, with various stellar masses, to study the impact of the bar on star formation history. Unbarred galaxies evolve very smoothly, with a star formation rate (SFR) that varies by at most a factor of three over a period of 2 Gyr. The evolution of barred galaxies is much more irregular, especially at high stellar masses. In these galaxies, the bar drives a substantial amount of gas toward the centre, resulting in a high SFR, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 96 publications
3
35
0
Order By: Relevance
“…Carles et al 2016). Because of large gas consumption along with the star formation in the past, the amount of gas and the gas metallicity of strongly barred galaxies are also expected to be currently low and high, respectively, consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Carles et al 2016). Because of large gas consumption along with the star formation in the past, the amount of gas and the gas metallicity of strongly barred galaxies are also expected to be currently low and high, respectively, consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Although at first instance our results seem at odds with these theoretical expectations, we explore two scenarios that can help to ease the discrepancy. First, Carles et al (2016) suggested that the star formation activity of barred galaxies could be triggered when the bars are formed and the SFRs of barred galaxies be- come similar to or lower than non-barred galaxies in 2 Gyrs; the difference between barred and non-barred galaxies would be larger strongly barred galaxies. The consumption of hydrogen gas is accelerated along with the star formation activity in barred galaxies, then the amount of gas in barred galaxies also becomes similar to or lower than for non-barred galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is especially important for the cases of B/T smaller than 0.1. The enhancement of the central SFR due to the presence of bars has been pointed out by several authors using observational data (de Jong et al 1984;Devereux 1987;Ellison et al 2011;Wang et al 2012;Florido et al 2015) and also in recent dynamical simulations such as in Carles et al (2016). As a result, a rejuvenation of the stellar populations in the center of barred galaxies has been also claimed by Fisher (2006) and Coelho & Gadotti (2011), among others.…”
Section: Sfr Ratios By Components: Sfr Central Enhancement Due To Thementioning
confidence: 66%
“…This exchange of angular momentum happens mainly by the bar resonances, transporting angular momentum from the inner region to outside corrotation (Lynden-Bell & Kalnajs 1972;Tremaine & Weinberg 1984a;Athanassoula 2003). Bars can induce a substantial amount of gas inflow, triggering star formation in the central regions (Hernquist & Mihos 1995;Martinet & Friedli 1997) possibly fueling the active galactic nucleus (Laine et al 2002), while quenching the inner kiloparsec region (Gavazzi et al 2015) and the rest of the galaxy E-mail: lgarma@astro.unam.mx (Carles et al 2016;Khoperskov et al 2018). Barred galaxies also tend to show flatten abundance profiles (Seidel et al 2016;Fraser-McKelvie et al 2019), resulting from the gaseous flows (Kubryk et al 2015) and stellar radial migration (Kubryk et al 2013;Di Matteo et al 2013).…”
Section: Introductionmentioning
confidence: 99%